Midwives Knowledge and Attitude on Infection Prevention and Control (IPC) - Gbadamosi, Faidat Temitope; Imran, Tesleem Omotayo; Olamijulo, Hellen (The Indonesian Institute of Science and Technology Research, 2024)
Infection prevention and control (IPC) is essential in reducing healthcare-associated infections, particularly in maternal and newborn care. Midwives play a critical role in ensuring adherence to IPC protocols in primary healthcare settings. This study aims to assess the knowledge, attitudes, and practices of midwives toward IPC in selected primary health care centers in Osogbo Local Government, Osun State, Nigeria. A cross-sectional survey was conducted among 52 midwives using a structured questionnaire to assess their knowledge and attitudes on IPC. The data were analyzed using descriptive statistics, with results presented as frequencies and percentages. The study found high IPC knowledge among midwives, with 96.2% classified as having good knowledge. Most participants demonstrated a strong understanding of key practices, such as hand hygiene, PPE use, and waste disposal. For example, 98.1% correctly identified the proper order for donning PPE, and all understood its primary purpose. However, 84.6% were aware of the recommended frequency for disinfecting high-touch surfaces, highlighting a gap in daily IPC practices. Midwives showed a positive attitude, with 88.5% agreeing that IPC guidelines reduce infection rates. Despite this, 9.6% felt resources were inadequate, and 84.6% called for more IPC training. The study shows strong IPC knowledge and positive attitudes among midwives, though gaps in resources and daily practices exist. Continuous training, better resource allocation, and fostering accountability are recommended to maintain high IPC standards. Targeted interventions should address these gaps and support midwives in effective IPC implementation.